Firewall fundamentals - Noonan, Wesley J. (Cisco, 2006)
The essential guide to understanding and using firewalls to protect personal computers and your network An easy-to-read introduction to the most commonly deployed network security device Understand the threats firewalls are designed to protect against Learn basic firewall architectures, practical deployment scenarios, and common management and troubleshooting tasks Includes configuration, deployment, and management checklists Increasing reliance on the Internet in both work and home environments has radically increased the vulnerability of computing systems to attack from a wide variety of threats. Firewall technology continues to be the most prevalent form of protection against existing and new threats to computers and networks. A full understanding of what firewalls can do, how they can be deployed to maximum effect, and the differences among firewall types can make the difference between continued network integrity and complete network or computer failure. Firewall Fundamentals introduces readers to firewall concepts and explores various commercial and open source firewall implementations--including Cisco, Linksys, and Linux--allowing network administrators and small office/home office computer users to effectively choose and configure their devices. Firewall Fundamentals is written in clear and easy-to-understand language and helps novice users understand what firewalls are and how and where they are used. It introduces various types of firewalls, first conceptually and then by explaining how different firewall implementations actually work. It also provides numerous implementation examples, demonstrating the use of firewalls in both personal and business-related scenarios, and explains how a firewall should be installed and configured. Additionally, generic firewall troubleshooting methodologies and common management tasks are clearly defined and explained.